2020
DOI: 10.1159/000507863
|View full text |Cite
|
Sign up to set email alerts
|

Pressure versus Sudden Wean from Nasal Continuous Positive Airway Pressure in Preterm Infants: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Nasal continuous positive airway pressure (NCPAP) is a well-studied treatment for respiratory problems in preterm infants. However, the best strategy for NCPAP weaning is unknown. <b><i>Objective:</i></b> We aimed to compare the success of progressive pressure wean versus sudden wean for discontinuation of NCPAP in preterm infants. <b><i>Methods:</i></b> We conducted a systematic review and meta-analysis of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Further, two systematic reviews that aimed to address this issue have shown a higher mean PMA of 32-33 weeks and mean weight of 1600-1770 g at the time of successful trial off nCPAP. 37,38 weeks) and higher weight (1600-1900 g) at successful trial off of nCPAP. 10,12,13,22 In these studies, investigators reported time to come off nCPAP for the whole study population without stratifying according to GA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, two systematic reviews that aimed to address this issue have shown a higher mean PMA of 32-33 weeks and mean weight of 1600-1770 g at the time of successful trial off nCPAP. 37,38 weeks) and higher weight (1600-1900 g) at successful trial off of nCPAP. 10,12,13,22 In these studies, investigators reported time to come off nCPAP for the whole study population without stratifying according to GA.…”
Section: Discussionmentioning
confidence: 99%
“…Further, two systematic reviews that aimed to address this issue have shown a higher mean PMA of 32–33 weeks and mean weight of 1600–1770 g at the time of successful trial off nCPAP 37,38 . Similarly, several randomized control trials have shown higher mean PMA (32–35 weeks) and higher weight (1600–1900 g) at successful trial off of nCPAP 10,12,13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of nCPAP weaning indicated that this method of abrupt cessation significantly reduced the PMA of successful weaning. [34][35][36] For a non-inferiority weaning study with the…”
Section: Discussionmentioning
confidence: 99%
“…We did not use lower pressures or cycling. A systematic review of nCPAP weaning indicated that this method of abrupt cessation significantly reduced the PMA of successful weaning 34–36. For a non-inferiority weaning study with the primary outcome being time of respiratory support, we chose a weaning method that resulted in the shortest time on support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation